2022
DOI: 10.1590/fst.57922
|View full text |Cite
|
Sign up to set email alerts
|

Biofunctional properties of the bioactive peptide from protein isolates of jiotilla (Escontria chiotilla) and pitaya (Stenocereus pruinosus) seeds

Abstract: In recent years, there has been considerable interest in bioactive peptides derived from food proteins, which might benefit human health. Pitaya and jiotilla are fruits with demonstrated biological functions in its stem, peel, and pulp. However, no studies have been conducted to evaluate the peptides. The aim of this study was to determine biofunctional properties (antioxidant, antihypertensive, and antidiabetic activities) of peptides from cacti seed protein. Antioxidant activity by ABTS, ACE inhibition activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…2 A). This efficacy parallels the high Ca-binding capacity observed in SBTH, indicating a correlation between Ca-binding and α-amylase inhibitory potential ( Sandate-Flores et al, 2022 ). However, during a simulation of gastrointestinal digestion, a decline in the inhibition rate was observed ( Fig.…”
Section: Resultssupporting
confidence: 56%
“…2 A). This efficacy parallels the high Ca-binding capacity observed in SBTH, indicating a correlation between Ca-binding and α-amylase inhibitory potential ( Sandate-Flores et al, 2022 ). However, during a simulation of gastrointestinal digestion, a decline in the inhibition rate was observed ( Fig.…”
Section: Resultssupporting
confidence: 56%
“…Thus, antioxidant (DPPH and FRAP assays) and antiproliferative (carcinogenic cell prevention) effects were detected in S. pruinosus juice that were explained by the presence of p -coumaric, gallic, caffeic, and vanillic acids [ 46 ]. Sandate-Flores et al [ 47 ] showed the antioxidant properties (ABTS assay) of seed peptides obtained from S. pruinosus by sequential hydrolyzation of glutelin fractions with pepsin and trypsin–chymotrypsin. During an in vivo study, Ramírez-Rodríguez et al [ 48 ] showed the antioxidant effect of S. huastecorum juice and explained it on the basis of the high content of betalains.…”
Section: Resultsmentioning
confidence: 99%